Computer Algebra in Scientific Computing : 19th International Workshop, CASC 2017, Beijing, China, September 18-22, 2017, Proceedings /: 19th International Workshop, CASC 2017, Beijing, China, September 18-22, 2017, Proceedings. (2017) - Unknown
No abstract available